EFFECT OF ALKALINE TREATMENTS IN LYE AND SLAKED LIME ON SOME NUTRIENTS, ANTINUTRIENTS AND IN VITRO PROTEIN DIGESTIBILITY OF EGYPTIAN RIVERHEMP (SESBANIA SESBAN) SEEDS - Arekemase , Shefiat O.; Abdulwaliyu , Ibrahim; Okoduwa, Stanley I.R.; Anigo, Kola M.; Ameh, Danladi A. (Food and Feed Research, 2022)
Sesbania sesban is widely distributed in different parts of Nigeria and is used as forage or green manure. However, the levels of antinutritional factors associated with the seed limit its use as an alternative feed for livestock. Therefore, this study determined the effect of alkaline treatments on some nutrient and antinutrient composition and in vitro protein digestibility of the seed of S. sesban. The seeds were treated by soaking (for 24 hours) and boiling (for 30 minutes) in slaked lime (calcium hydroxide) or lye. Afterwards, the boiled and soaked samples were properly dried at room temperature. The samples were then analysed using standard methods for proximate analysis, antinutrients, and in vitro protein digestibility. It was revealed that crude protein content was significantly (psoaking in lye. The seeds of S. sesban, if properly processed using lye, could serve as a potential alternative compound for livestock feed. The results of this research confirmed that treatments with lye, which is much less costly and more available to rural communities are comparable to those based on slaked lime and can be used interchangeably.
Keywords: ash; boiling; calcium hydroxide; soaking; tannins; tripsin inhibitor